Microbiological aspects of the biofilm on wooden utensils used to make a Brazilian artisanal cheese - Galinari, Éder (Sociedade Brasileira de Microbiologia, 2014)
The artisanal Minas cheese is produced from raw cow’s milk and wooden utensils were employed in its manufacture, which were replaced by other materials at the request of local laws. This substitution caused changes in the traditional characteristics of cheese. Due to the absence of scientific studies indicating the microbial composition of biofilms formed on wooden forms, tables and shelves used in these cheese production, the present work evaluated the counts of Staphylococcus aureus, Escherichia coli, coliforms at 32 °C, yeasts, presumptive mesophilic Lactobacillus spp. and Lactococcus spp. in these biofilms, milk, whey endogenous culture and ripened cheese in two traditional regions: Serro and Serra da Canastra. Also, we checked for the presence of Salmonella sp. and Listeria monocytogenes in the ripened cheeses. The ultra structure of the biofilms was also assessed. Counts above legislation (> 2 log cfu/mL) for the pathogens evaluated were found in milk samples from both regions. Only one shelf and one form from Serro were above limits proposed (5 cfu/cm(2) for S. aureus and E. coli and 25 cfu/cm(2) for coliforms) in this study for contaminants evaluated. In Canastra, few utensils presented safe counting of pathogens. There was no Salmonella sp. and Listeria monocytogenes in the cheeses after ripening. Thus, the quality of the cheese is related to improving the microbiological quality of milk, implementation and maintenance of good manufacturing practices, correct cleaning of wooden utensils, and not its replacement.